Primary Orbital Mesenchymal Chondrosarcoma: Case Report and Review of the Literature - Angel Herrera; Cesar Ortega; Gervith Reyes; Miguel Angel Alvarez; Daniela Tellez (Case Reports in Medicine)
Orbital mesenchymal chondrosarcoma is a very uncommon lesion of the bone and extraskeletal tissue. To our knowledge, approximately 30 cases have been described. We present the case of a 52-year-old male who presented with a history of progressive proptosis and chemosis of the right eye caused by an orbital tumor. He underwent exenteration of the right orbit, and the histological examination revealed a mesenchymal orbital chondrosarcoma. This paper attempts to describe a rare entity that should be considered in the differential diagnosis of calcified orbital lesions, especially in young adults. Complete removal of the tumor is the mainstay of treatment, but adjuvant radiation therapy and chemotherapy should be considered.